Perancangan dan Implementasi Informational Dashboard untuk Monitoring dan Evaluasi Kegiatan Belajar Mengajar di Politeknik Caltex Riau - Dini Nurmalasari; Zusanti Syahrial (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Informational dashboard design aims to design a visualization model of information for the needs of monitoring and evaluation process of teaching and learning activities at the Polytechnic Caltex Riau. Dashboard is a visualization of an information system that can provide information on the main indicators of an organization's or institution’s activity. In this study the information presented is the main indicators of themonitoring and evaluation (Monev) process of learning and teaching at Polytechnic institutions Caltex Riau (PCR). Monev process is carried out continuously by PCR institution to ensure and guarantee the quality of the learning process that takes place in the PCR. Results from the design and implementation of informational dashboard provide information regarding the activities of learning and teaching in PCR institutional environment in attractive and easy to understand form. The information presented on this dashboard information is tailored to the needs of top-level management, which is expected to help in the decision process.Keywords: Business Intelligent , Informational Dashboard, Monitoring and Evaluation Academic,